2015
DOI: 10.1016/j.ejvs.2014.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Ultrasound Evaluation of Small Asymptomatic Abdominal Aortic Aneurysms

Abstract: 3D-US demonstrated an acceptable reproducibility and a good agreement with 3D-CT, and has the potential to improve future AAA management through more reliable ultrasound guided size estimates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 17 publications
2
54
0
1
Order By: Relevance
“…On the transverse image, the calipers were adjusted from the leading edge of the adventitia anterior wall to the leading edge of the adventitia posterior wall (LELE) as previously described. 12 The dual plane technique is established as the first line measure of AAA diameter and has been validated and described previously. 12…”
Section: Dual Plane B-mode Ultrasoundmentioning
confidence: 99%
“…On the transverse image, the calipers were adjusted from the leading edge of the adventitia anterior wall to the leading edge of the adventitia posterior wall (LELE) as previously described. 12 The dual plane technique is established as the first line measure of AAA diameter and has been validated and described previously. 12…”
Section: Dual Plane B-mode Ultrasoundmentioning
confidence: 99%
“…9 However, there have been few US studies of the biomechanical wall properties of AAA reported in the literature, 10,11 as well as few studies showing the use of three-dimensional ultrasound (3D-US) imaging to evaluate aneurysm volume quantification. 12,13 The aim of this study was to assess the ability of the US coupled with two-dimensional (2D) speckle-tracking algorithms to evaluate biomechanical properties of the aorta in patients with and without AAA. The secondary objective was to measure the AAA partial volume by the 3D-US, and compare it with the volume estimated by CT.…”
Section: Introductionmentioning
confidence: 99%
“…3D-US has been investigated in three studies from two centres with the aim of improving the accuracy of measuring maximum diameter assessment in AAA and EVAR surveillance. 2,3,13 Using the same semi-automated software, two types of maximum diameter were described in each of these studies: (1) the US dual-plane diameter was determined on the US unit at the bedside using existing software on the US system where transverse and longitudinal views were displayed simultaneously in a live split image ( Fig. 2); (2) the centreline diameter was defined "off line" on a workstation as the maximum diameter perpendicular to a centreline, semi-automatically generated in postprocessing software ( Fig.…”
Section: Measuring Aaa Sizementioning
confidence: 99%
“…Most importantly, reproducibility was superior compared with the conventional 2D-US anteroposterior diameter. 2 The time spent on postprocessing in order to determine the centreline diameter has been recently reduced to a promising median of 72 s, using software expected to become commercially available soon. Ease and speed, which is critical if these methods are expected to become standard in clinical practice, is expected to improve in the coming few years.…”
Section: Measuring Aaa Sizementioning
confidence: 99%